Natura 2000 habitat of Mt. Argentario promontory (southern Tuscany, Italy). Issue 2 (13th November 2018) - Viciani, Daniele; Dell'Olmo, Lorella; Foggi, Bruno; Ferretti, Giulio; Lastrucci, Lorenzo; Gennai, Matilde
ABSTRACT: The Mt. Argentario promontory (southern Tuscany, Italy) is a protected area hosting habitats and species of European importance. The Mt. Argentario Natura 2000 habitat map (1:10, 000) was compiled from photo-interpretation and field surveys, integrated with data from past cartographic and phytosociological studies. Conventional geographical information system procedures were used to select and manage spatial information, and delimit the map polygons. The following attributes were assigned to each map polygon: (i) habitat type name, with Natura 2000 code and (ii) percentage cover of the habitat type. Where multiple habitat types were associated in a mosaic attributed to the same polygon, the percentage cover of each habitat type was estimated. The survey allowed to identify and map a total of 13 Natura 2000 habitat types covering more than 40% of the study area. Presence and conservation importance of the detected habitat types are discussed, together with the usefulness of this kind of maps for monitoring and managing purposes.